Uso de matlab y simulink para el control de robots y la observación de sensores de tacto y ultrasónico - Aguirre Patiño, Martha Isabel (2009)
This project uses the Lego Mindstorms NXT Kit to develop an application that emphasizes the use of certain sensors of the Kit using the Matlab software. The design is the representation of an explorer robot, which will be able to move freely on a determined area defined by the user. The robot will avoid obstacles and take independent decisions. Part of his process will be donned using an ultrasonic sensor, which detects nearby objects; in addition a touch sensor has been located in the lower part of the robot to avoid collisions that cannot be detected by the ultrasonic sensor. The program to move the robot was developed using Simulink, a Matlab tool that allows a block programming approach for the robot movements. Afterwards the program is loaded into the NXT brain. This robot was designed not only to control movements but also to serve as a data acquisition unit of a variable that will be shown to the user later. This variable represents sound data. In this case a sound sensor was used to capture noise levels, in decibels, from the environment. The capture data is sent from the Lego Mindstorm robot through a Bluetooth interface to the computer where it will be processed using a program developed in Matlab. The data will be presented later on a graphic interface. On this interface the acquired data will be shown on a graphic window with the option to save the data on an Excel sheet or a .bmp file. This will allow the user to create a database with the sensing information. The final result it will be an explorer robot that can take movement decisions and make data acquisitions at the same time.